Dynamics coupling analysis between elastic supporting structure and TLD with and without slat screen. (December 2022) - Zheng, Jinhai; Dou, Peng; Xue, Mi-An
Abstract: The slat screen (SS) has been widely used in tuned liquid damper (TLD) to increase damping and suppress structural vibration. This study proposes a linked-spring screen that has a movable screen elastically connected to the inner wall. Laboratory experiments of elastic supporting structure with TLD were first conducted on a hexapod table to obtain structural dynamics response under different conditions. Wavelet transform and wavelet-based bicoherence are used to analyze the nonlinear characteristics of sloshing waves. Meanwhile, a two-way coupling numerical model was validated to accurately predict the nonlinear coupling interaction between structure and TLD. Effects of the SS on reducing the structural vibration were numerically evaluated together with the interactions among elastic structure, TLD and SS. Finally, effects of spring stiffness on TLD with linked-spring screen were studied. Findings show that SS can not only enhance the internal dissipation by creating vortexes but also break waves through the perforation. Compared with conventional TLD, screen with S e = 0.75 and D / L = 0.15 can reduce the maximum displacement by 37.86 %. Besides, the linked-spring screen can further improve the damping performance because of the enhanced shear flow and turbulence intensity when it was moving. The optimal damping effect can be achieved for K = 500 N·m −1 where the further reduction ratio is 29.80 %.